Isolating a trimer intermediate in the self-assembly of E2 protein cage - Peng, Tao (2013)
Understanding the self-assembly mechanism of caged proteins provides clues to develop their potential applications in nanotechnology, such as a nanoscale drug delivery system. The E2 protein from Bacillus stearothermophilus, with a virus-like caged structure, has drawn much attention for its potential application as a nanocapsule. To investigate its self-assembly process from subunits to a spherical protein cage, we truncate the C-terminus of the E2 subunit. The redesigned protein subunit shows dynamic transition between monomer and trimer, but not the integrate 60-mer. The results indicate the role of the trimer as the intermediate and building block during the self-assembly of the E2 protein cage. In combination with the molecular dynamics simulations results, we conclude that the C-terminus modulates the self-assembly of the E2 protein cage from trimer to 60-mer. This investigation elucidates the role of the intersubunit interactions in engineering other functionalities in other caged structure proteins.